FORMULA ALTERNATIF DANA ALOKASI UMUM - Edy Suandi Hamid (Journal of Indonesian Economy and Business (JIEB), 2003)
The objectives of this study is to formulate a transfer formula of fund from the central government to regional governments, especially the general purpose transfers or general allocation funds (Dana Alokasi Umum/DAU) to fulfill the normative criteria of Law No. 25/1999 by considering the condition of human development at the regions. The formula can be used to equalize interregional fiscal capacities, and to analyze the impact of DAU transfer to the regional revenue equalization, by using the indicators of variation coefficient and Williamson’s index. The fiscal gap approach is used to formulate DAU Formula. The impact of the DAU Formula to interregional revenue equalization is calculated by simulating variation coefficient and Williamson’s index.This study found that the DAU IPM Formula, using human development variables is more appropriate for Indonesia as a substitute to the current DAU Formula. From the simulation this DAU IPM Formula result in a better rate of fiscal equalization, especially for the districts/municipalities.Keywords: Transfer formula, General Allocation Funds, DAU Formula, Human development, Variation coefficient, Williamson’s index, Interregional revenue equalization.